Loss aversion in social image concerns - Vasilisa Petrishcheva; Gerhard Riener; Hannah Schildberg-Hörisch (ZBW - Leibniz Information Centre for Economics, 2020)
We conduct a laboratory experiment to explore whether loss aversion applies to social image concerns. First, subjects are ranked publicly in a social image relevant domain, an IQ test, to establish own rank as a within-subject reference point. We then induce an exogenous change in within-subject rank and offer scope for lying about it to test whether subjects whose rank exogenously deteriorates (loss in social image) lie more than those who experience an equally-sized gain in rank (gain in social image). We find evidence for loss aversion in social image concerns, however, only for subjects who strongly care about their social image and have reputation to lose (high initial reference point).
Keywords: C91; D91; 330; loss aversion; social image concerns; lying behavior; laboratory experiment